Diversity and community structure of microzooplankton in the eastern Indian Ocean during the inter-monsoon period - Zhai, Jian; Sun, Jun (Frontiers in Marine Science, 2023)
Microzooplankton (MZP) are an important part of the microbial food web and play a pivotal role in connecting the classic food chain with the microbial loop in the marine ecosystem. They may play a more important role than mesozooplankton in the lower latitudes and oligotrophic oceans. In this article, we studied the species composition, dominant species, abundance, and carbon biomass of MZP, including the relationship between biological variables and environmental factors in the eastern equatorial Indian Ocean during the spring intermonsoon. We found that the MZP community in this ocean showed a high species diversity, with a total of 340 species. Among these, the heterotrophic dinoflagellates (HDS) (205 species) and ciliates (CTS) (126 species) were found to occupy the most significant advantageous position. In addition, CTS (45.3%) and HDS (39.7%) accounted for a larger proportion of the population abundance, while HDS (47.1%) and copepod nauplii (CNP) (46.4%) made a larger contribution to the carbon biomass. There are significant differences in the ability of different groups of MZP to assimilate organic carbon. In this sea area, MZP are affected by periodic currents, and temperature is the main factor affecting the distribution of the community. The MZP community is dominated by eurytopic species and CNP. CTS are more sensitive to environmental changes than HDS, among which Ascampbelliella armilla may be a better habitat indicator species. In low-latitude and oligotrophic ocean areas, phytoplankton with smaller cell diameters were found to occupy a higher proportion, while there was no significant correlation between the total concentration of integrated chlorophyll a and the biological variables of MZP. Therefore, we propose that the relationship between size-fractionated phytoplankton and MZP deserves further study. In addition, the estimation of the carbon biomass of MZP requires the establishment of more detailed experimental methods to reflect the real situation of organisms. This study provides more comprehensive data for understanding the diversity and community structure of MZP in the eastern equatorial Indian Ocean, which is also of good value for studying the adaptation mechanism and ecological functions of MZP in low-latitude and oligotrophic ocean ecosystems.